Manajemen Ekstra Kurikuler Hizbul Wathan Dalam Pengembangan Nilai-Nilai Karakter di SMK - Narimo, Sabar; Irawan, Endra Purna (Manajemen Pendidikan, 2018)
This study aims to describe: 1) the preparation of extracurricular activitiesprogram Hizbul Wathan to develop character values in SMK Muhammadiyah 4Surakarta. Types of qualitative research with ethnographic design Data collectiontechniques: interviews, observation and documentation. Data validity with technicaltriangulation and source triangulation. Data analysis using three stages, namely datareduction, data presentation, and conclusion drawing with verification. The resultsshowed: 1) Preparation of the Hizbul Wathan extracurricular activity program atSMK Muhammadiyah 4 Surakarta, consisting of (a) extracurricular activities ofHizbul Wathan, (b) elaboration of the vision, mission and objectives of the school,(c) Preparation of extracurricular activities program Hizbul Wathan must be inaccordance with the vision, mission, and objectives of the school’s Decree, (d) (SK)division of tasks as coach, (e) funds sourced from School Operational Assistance(BOS).